(untitled) (Research, Society and Development, 2022)
Leprosy is a chronic, infectious disease whose etiologic agent is Mycobacterium leprae, an intracellular parasite with tropism for cutaneous macrophages and Schwann cells of the peripheral nervous system. Worldwide, 210,758 new cases were diagnosed in 2015. The present study aims to analyze leprosy and its clinical management. This is an integrative literature review, carried out through the Virtual Health Library (VHL) in Pubmed databases, using the crossings of the English descriptors “Leprosy”, “Epidemiology”. To evaluate the research problem and its stratification, the PVO strategy (Population/Problem, Variable/Results and Outcomes/Outcomes) was used, with the following strategy being formulated. The aforementioned strategy allowed us to formulate the following guiding question: "How is the clinical management of leprosy performed?". Leprosy can present in different ways, depending on the immune response of the infected individual. The main signs and symptoms of leprosy are: areas of skin, or whitish (hypochromic), brownish or reddish patches, with changes in sensitivity to heat and/or painful, and/or to touch; it hurts without realizing it; Papules, tubercles and nodules (lumps), usually without symptoms; Decreased or shedding of hair, localized or diffuse, especially in the eyebrows (madarosis); Infiltrated (reddish) skin, with decrease or absence of sweat at the site. Measures against leprosy must continue and be intensified in regions with the greatest aggravations, aiming at an effective homogeneous control of the disease.